Pengelolaan Event Pameran Berbasis Collaborative Governance : (Studi Kasus pada Kegiatan Pameran Baby & Kids Expo 2020) - Sunmedar Rachmat; Elly Malihah; Rini Andari (Politeknik Pariwisata NHI Bandung, 2023)
This study aims to analyze exhibition management in a case study of the Baby & Kids Expo 2020 exhibition activities based on collaborative governance. Trade is the second largest sector contributing to economic development in Indonesia. Exhibition or exhibition is one of the events used to increase a company's income through buying and selling transactions in the trade sector. Currently, the market size for baby equipment in Indonesia reaches Rp. 10.4 trillion, the Baby & Kids Expo exhibition is here to take advantage of this momentum. Of course the implementation of the Baby & Kids Expo exhibition was carried out not only because of the government's intervention in it but because of the support of various stakeholders. This stakeholder collaboration is then known as collaborative governance. This research seeks to see the role and collaboration that exists between various stakeholders in the management of the Baby & Kids Expo exhibition event based on collaborative governance.